(untitled) (Praxis Educativa, 2022)
This article addresses the learning that occurs in the context of the productive practices developed by a group of agroecological producers organized in the Orillerxs Collective. Is part of the initiatives of a university team that proposed forms of co-production of knowledge, and of a doctoral research project. In this framework, a qualitative methodological strategy was carried out, taking some tools from the current of ethnography with the aim of inquiring about the knowledge built by the producers in the collective work process. The research findings show that there is a multiplicity of learning that has been built in the collective work process. Among them, we highlight four types: technical-productive learning; the operations put into play, the learning about agroecological production and the collective learning.